Plasma‐Assisted Surface Modification and Heparin Immobilization: Dual‐Functionalized Blood‐Contacting Biomaterials with Improved Hemocompatibility and Antibacterial Features. Issue 6 (4th December 2022) - Özgüzar, Hatice Ferda; Evren, Ebru; Meydan, Ahmet Ersin; Kabay, Gozde; Göçmen, Julide Sedef; Buyukserin, Fatih; Erogul, Osman
Abstract: The inferior hemocompatibility or antibacterial properties of blood‐contacting materials and devices are restraining factors that hinder their successful clinical utilization. To highlight these, a plasma‐enhanced modification strategy is favored for surface tailoring of an extensively used biomaterial, polypropylene (PP). The surface activation of the PPs is achieved by oxygen plasma etching and subsequent surface functionalization through amine‐rich precursor mediated coating by plasma glow discharge. After optimum plasma processing parameters are decided, heparin (anticoagulant and antithrombic drug) is either attached or covalently conjugated on the PPs' surfaces. The aminated films produced at 75 W plasma power with 15 min exposure time are highly hydrophilic (34.72 ± 5.92°) and surface active (65.91 mJ m −2 ), facilitating high capacity heparin immobilization (≈440 µg cm −2 ) by covalent linkage. The kinetic‐blood coagulation rate and protein adhesion amount on the plasma‐mediated heparinized PPs are decreased about tenfold and 15‐fold, and platelet adhesion is markedly lowered. In addition, heparinized‐PP surfaces comprise superior antibacterial activity against gram‐positive/‐negative bacteria conveyed particularly by contact‐killing (99%). The heparin‐coating did not cause cytotoxicity on fibroblast cells, instead enhanced their proliferation, as shown by the (3‐(4, 5‐Dimethylthiazol‐2‐yl)‐2, 5‐Diphenyltetrazolium Bromide) assay. Overall, this simple methodology is highly proficient in becoming a universal strategy for developing dual‐functionalized blood‐contacting materials. Abstract : The host immune system generates an immune response against an implanted material with insufficient hemocompatibility and antibacterial properties. To avoid this, the authors present a single‐step plasma‐mediated heparinization scheme. The proposed strategy successfully enhances the deficient features of conventional polypropylene. Consequently, this modification strategy has shown promise to become a universal method that facilitates the clinical translation of blood‐contacting materials.